Cultural Transformation in Religious Activities Based on Ahlussunnah Wal Jama'ah Values in Islamic Boarding Schools - Ike Nur Jannah; Rodliyah Rodliyah; Lailatul Usriyah (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
This article describes and analyzes implementing ahlussunnah wal-jamaah values through religious activities and culture at the Al-Ikhlas Wuluhan Islamic boarding school, Jember Regency, East Java: data collection techniques utilized observation, interviews, and documentation studies. The stages in question follow the pattern of the reduction stage, the stage of presenting data, making temporary conclusions, and verification activities. The research findings conclude that two values become the vision and mission of the Al-Ikhlas Wuluhan Islamic boarding school; first, the value of human beings, namely the teaching that students must balance between religion and the world; in other words, Islam does not only pay attention to the afterlife issues but also pays attention to worldly problems, the second is the value of brotherhood or ukhuwah basyariyah, namely brotherhood that applies to all human beings universally without distinguishing race, religion, ethnicity and other aspects of specificity with the details of the rights of fellow human beings in property by taking into account the needs of their siblings with excess wealth, the rights of fellow human beings in guarding speech. While the religious activities carried out by the Al-Ikhlas Wuluhan Jember Islamic Boarding School in improving the ahlussunnah wal-jama'ah character of the students are internal activities carried out and attended by only the core students, internal activities include sorogan al-Qur'an, mudzakarah, evening dhikr, and khidmad. In contrast, core and village students carry out and participate in external activities, namely pencak silat activities.